Outside Front Cover: Volume 4 Issue 1. Issue 1 (26th December 2022) - Fan, Xiao‐Chun; Wang, Kai; Shi, Yi‐Zhong; Sun, Dian‐Ming; Chen, Jia‐Xiong; Huang, Feng; Wang, Hui; Yu, Jia; Lee, Chun‐Sing; Zhang, Xiao‐Hong
Abstract : Outside front cover image : Two thermally activated delayed fluorescence molecules are designed by strategically integrating three effective strategies: 1) bulky peripheral side groups; 2) "self‐doping" configuration induced by dual conformation; 3) highly ordered horizontal orientations. Nondoped OLEDs using the two new emitters deliver 100% exciton utilization, record‐high maximum EQEs of over 30% and ultralow efficiency roll‐off for the first time. (DOI: https://doi.org/10.1002/smm2.1122 )